Use of Flexible Cystoscopy to Insert a Foley Catheter over a Guide Wire in Spinal Cord Injury Patients: Special Precautions to be Observed - Subramanian Vaidyanathan; Bakul Soni; Gurpreet Singh; Peter Hughes; Tun Oo (Advances in Urology)
When urethral catheterisation is difficult or impossible in spinal cord injury patients, flexible cystoscopy and urethral catheterisation over a guide wire can be performed on the bedside, thus obviating the need for emergency suprapubic cystostomy. Spinal cord injury patients, who undergo flexible cystoscopy and urethral catheterisation over a guide wire, may develop potentially serious complications. (1) Persons with lesion above T-6 are susceptible to develop autonomic dysreflexia during cystoscopy and urethral catheterisation over a guide wire; nifedipine 5–10 milligrams may be administered sublingually just prior to the procedure to prevent autonomic dysreflexia. (2) Spinal cord injury patients are at increased risk for getting urine infections as compared to able-bodied individuals. Therefore, antibiotics should be given to patients who get haematuria or urethral bleeding following urethral catheterisation over a guide wire. (3) Some spinal cord injury patients may have a small capacity bladder; in these patients, the guide wire, which is introduced into the urinary bladder, may fold upon itself with the tip of guide wire entering the urethra. If this complication is not recognised and a catheter is inserted over the guide wire, the Foley catheter will then be misplaced in urethra despite using cystoscopy and guide wire.